Potential considerations in decision making on laparoscopic colorectal resections in Hungary based on administrative data. - Zsófia Benedek (Public Library of Science (PLoS), 2021)
Background Laparoscopic colorectal surgeries offer numerous advantages over their open counterparts. To compare these measurable short-time outcomes of open and laparoscopic resections in Hungary, data of colorectal surgeries were collected and analysed. The study focused on identifying patients' characteristics that can influence the decision on laparoscopic colorectal resections and on comparing efficiency of Hungarian colorectal operations with international data. Methods Using patients' data of laparoscopic and open colorectal surgery performed in 2015 and 2016 from the National Health Insurance Fund of Hungary, a countrywide retrospective comparative analysis was done. Logistic regression was used to explore main influencing factors for laparoscopic colorectal surgery. Results A total of 17,876 colorectal surgical cases, including 14,876 open and 3,000 laparoscopic resections were selected and analysed. Laparoscopy was used only in 16.78% of all cases. Comparison of age groups showed that odds ratio (OR) of laparoscopic colorectal resections was significantly lower in over 40 years than in younger patients (18-39 years). In university institutes patients had higher odds (OR: 2.23 p<0.0001) for laparoscopic colorectal resections. Presence of comorbidity codes and preoperative treatment in internal medicine department decreased odds for laparoscopic colorectal operations. Conclusions Patients' age, comorbidities and hospital type influenced the likelihood of decision on laparoscopic colorectal resection. Selection of patients contributed to improved laparoscopic outcomes.